Identification and Comparative Analysis of Venom Proteins in a Pupal Ectoparasitoid, Pachycrepoideus vindemmiae - Yang, Lei; Yang, Yi; Liu, Ming-Ming; Yan, Zhi-Chao; Qiu, Li-Ming; Fang, Qi; Wang, Fang; Werren, John H.; Ye, Gong-Yin (Frontiers in Physiology, 2020)
Parasitoid wasps inject venom containing complex bioactive compounds to regulate the immune response and development of host arthropods and sometime paralyze host arthropods. Although extensive studies have been conducted on the identification of venom proteins in larval parasitoids, relatively few studies have examined the pupal parasitoids. In our current study, a combination of transcriptomic and proteomic methods was used to identify 64 putative venom proteins from Pachycrepoideus vindemmiae, an ectoparasitoid of Drosophila. Expression analysis revealed that 20 tested venom proteins have 419-fold higher mean expression in the venom apparatus than in other wasp tissues, indicating their specialization to venom. Comparisons of venom proteins from P. vindemmiae and other five species spanning three parasitoid families detected a core set of “ancient” orthologs in Pteromalidae. Thirty-five venom proteins of P. vindemmiae were assigned to the orthologous groups by reciprocal best matches with venoms of other pteromalids, while the remaining 29 were not. Of the 35 categories, twenty-seven have orthologous relationships with Nasonia vitripennis venom proteins and 25 with venoms of Pteromalus puparum. More distant relationships detected that five and two venom proteins of P. vindemmiae are orthologous with venoms of two Figitidae parasitoids and a Braconidae representative, respectively. Moreover, twenty-two venoms unique to P. vindemmiae were also detected, indicating considerable interspecific variation of venom proteins in parasitoids. Phylogenetic reconstruction based on a set of single-copy genes clustered P. vindemmiae with P. puparum, N. vitripennis, and other members of the family Pteromalidae. These findings provide strong evidence that P. vindemmiae venom proteins are well positioned for future functional and evolutionary studies.